Effect of power output on muscle coordination during rowing - Turpin, N. A.; Guével, A.; Durand, S.; Hug, F. (European Journal of Applied Physiology, 2011)
The present study was designed to quantify the effect of power output on muscle coordination during rowing. Surface electromyographic (EMG) activity of 23 muscles and mechanical variables were recorded in eight untrained subjects and seven experienced rowers. Each subject was asked to perform three 2-min constant-load exercises performed at 60, 90 and 120% of the mean power output over a maximal 2,000-m event (denoted as P60, P90, and P120, respectively). A decomposition algorithm (nonnegative matrix factorization) was used to extract the muscle synergies that represent the global temporal and spatial organization of the motor output. The results showed a main effect of power output for 22 of 23 muscles (p values ranged from <0.0001 to 0.004) indicating a significant increase in EMG activity level with power output for both untrained and experienced subjects. However, for the two populations, no dramatic modification in the shape of individual EMG patterns (mean r max value = 0.93 ± 0.09) or in their timing of activation (maximum lag time = -4.3 ± 3.8% of the rowing cycle) was found. The results also showed a large consistency of the three extracted muscle synergies, for both synergy activation coefficients (mean r max values range from 0.87 to 0.97) and muscle synergy vectors (mean r values range from 0.70 to 0.76) across the three power outputs. In conclusion, despite significant changes in the level of muscle activity, the global temporal and spatial organization of the motor output is very little affected by power output on a rowing ergometer. see: http://www.rspdl.com/web/fichiers/pdf/Turpin_et_al_EJAP_2011.pdf